THE DEVELOPMENT OF TRANSFORMATIVE ART LEARNING MODEL FOR ENHANCING PUBLIC MIND VALUE - Laosat, Chaiwattanapat; Sangvanich, Khanobbhorn (Journal of Social Science and Cultural, 2023)
The purpose of this research was to develop, use, and validate the transformation art learning model for enhancing public mind value. The learning model is generated by using the participatory learning and action research (PLAR) among six key stakeholder groups: 1) the art teachers 2) the community leaders 3) the academicians from non-government organizations and private sectors 4) the academicians from government organizations 5) the local artists 6) the students under bachelor’s degree program in visual art and design, who are involved in development and evaluate the learning model in 3 cycles. The sample groups were 25 students under bachelor’s degree program in visual art and design. The research instruments consisted of lesson plans, public mind values test, reflective dialogue, student satisfaction survey form and community satisfaction survey form. The results showed as follows: 1) The results of learning model development were found that the main principles of the transformative art learning model for enhancing public mind value are holistic learning management, connect students with the community, learning from a good role model, creating opportunities to use art knowledge for benefit of society, and internal reflection through art. 2) After implementing the learning model the results from public mind test revealed that the post-test mean scores of the sample groups were higher than the pre-test mean scores at a significant difference of .05 3) student reflect on their feelings of wanting to participate in contributing to society and take pride in applying art knowledge for society development 4) The community 's satisfaction toward the student 's artworks at the highest level 5) The student 's satisfaction toward learning model at high level.